Pondok Pesantren dan Dakwah Politik: Kajian Histori Pondok Pesantren Hasyim Asy’ari Bangsri Jepara - Siti Asiyah; Arif Chasanudin (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2020)
Political Da'wah at the Islamic boarding school (pesantren) is an interesting theme that needs to be discussed. Many people have a perception that Islamic boarding school and Political Da'wah are separated from each other. The purpose of this study was to analyze the efforts of Hasyim Asy'ari Islamic Boarding School in embed political da'wah to students and the role of caregivers in applying political da'wah towards students and the community. This research was conducted with a historical qualitative approach. The results of this study are, Islamic Boarding School Hasyim Asy'ari in an effort to embed Political Da'wah to students by (1) learning about leadership and politics in pesantren, (2) conducting leadership training, (3) applying political culture. In addition, the role of caregivers (pengasuh) in carrying out Political Da'wah to students (santri) is seen in religious teaching by embedding spiritual, moral and social values as a provision for students to face social life. The role of caregivers in carrying out political da'wah to the public is by serving as an official in the government, caregivers are able to provide knowledge to the public about the importance of politics and the political system of the country, the role of government in making policies, and participation in political activities (balanced between rights and obligations as citizens), so that the public is aware of the importance of politics and is able to choose leaders who are competent and trustworthy. Dakwah Politik yang di lakukan di pondok pesantren menjadi tema menarik yang perlu dibahas karena banyak orang memiliki persepsi bahwa pondok pesantren dan dakwah politik memiliki sekat yang tidak mampu disatukan. Tujuan penelitian ini adalah melakukan analisis terhadap upaya Pondok Pesantren Hasyim Asy’ari dalam penanaman dakwah politik kepada santri serta peran pengasuh dalam menerapkan dakwah politik kepada santri dan masyarakat. Penelitian ini dilakukan dengan pendekatan kualitattif historis. Hasil kajian ini membuktikan bahwa, Pondok Pesantren Hasyim Asy’ari dalam upaya penanaman dakwah politik kepada santri dengan cara (1) melakukan pembelajaran tentang kepemimpinan dan politik di pesantren, (2) mengadakan pelatihan kepemimpinan, (3) menerapkan budaya politik. Selain itu, peranan pengasuh dalam melakukan dakwah politik kepada santri dapat dilihat dalam mengajarkan pendidikan agama dengan menanamkan nilai-nilai spiritual, moral dan sosial kemasyarakatan sebagai bekal santri dalam menghadapi kehidupan bermasyarakat. Adapun peranan pegasuh dalam melakukan dakwah politik kepada masyarakat yaitu dengan mengabdikan diri sebagai pejabat di pemerintahan, pengasuh mampu memberikan pengetahuan kepada masyarakat tentang pentingnya politik dan sistem politik negara, peran pemerintah dalam membuat kebijakan, serta pasrtisipasi dalam kegiatan politik (seimbang antara hak dan kewajiban sebagai warga negara), sehingga masyarakat sadar akan pentingnya politik dan mampu memilih pemimpin yang kompeten dan amanah.